Pengaruh Pembelajaran Outdoor terhadap Pemahaman Konsep Fotosintesis pada Siswa Sekolah Dasar - Shafa Mulia Aryadewi; Sardin Sardin (Journal on Education, 2025)
This study aims to analyze the impact of outdoor learning on elementary school students' understanding of the photosynthesis concept. A quasi-experimental method with a non-equivalent group design was employed, involving an experimental group and a control group. The experimental group participated in outdoor learning-based activities, while the control group received conventional teaching. Data were collected through pre-test and post-test assessments. The results indicate that outdoor learning significantly enhances students' comprehension of photosynthesis compared to conventional methods. Additionally, students were more motivated, enthusiastic, and engaged during the learning process. The study concludes that outdoor learning is an effective approach to improving students' understanding, especially in photosynthesis topics, and recommends its broader implementation in elementary schools.